Consumption of beef sandwiches in the United States and contributions to intake of energy and select nutrients - Murphy, Mary M.; Anderson, Maribeth M.; Bi, Xiaoyu (Frontiers in Nutrition, 2024)
Introduction Sandwiches are commonly consumed in the United States. This study summarizes contributions of beef sandwiches to energy and select nutrient intakes. Methods Beef sandwiches were categorized as beef burger sandwiches (hamburgers or cheeseburgers) and non-burger beef sandwiches. Per capita and per user consumption of beef sandwiches (total and by type) and contributions to total nutrient intakes from beef and non-beef sandwich components were estimated for the population ages ≥2 years (n = 15,984) participating in WWEIA/NHANES, 2013–2016. Results On any given day, 21.4% of the population consumed a beef sandwich. Among all Americans, beef sandwiches provided 6.3% of mean energy intake and accounted for approximately 10% of the population’s mean intake of vitamin B12 and saturated fat, 9% of protein and sodium, 7% of iron, 6% of choline, and 5% of potassium. Among beef sandwich consumers, beef sandwiches accounted for 26.2% of mean energy intake on a day of consumption. The beef component of sandwiches accounted for the majority of vitamin B12, choline, and protein, non-beef components accounted for the majority of sodium, iron, and potassium, and beef and non-beef components made similar contributions to saturated fat. Hamburgers provided consumers the lowest energy, sodium, and saturated fat intake, while non-burger sandwiches provided the highest intake of these nutrients. Discussion Beef sandwiches are an important source of energy, protein, vitamin B12, iron, and choline, and like other sandwiches, are also a source of sodium and saturated fat. Americans could enhance nutrient contributions from sandwiches by selecting lean meat and limiting use of saturated fat- or sodium-rich non-beef components.